An Empirical Analysis of Invalid Voting in Municipal Elections. - Castro, Vítor; Martins, Rodrigo; Sakurai, Sergio Naruhiko (Kyklos, 2025)
This paper examines blank and null voting in Brazilian mayoral elections using a large dataset covering 5570 municipalities between 2000 and 2020. The study finds that more competitive elections reduce blank and null percentages, with re‐election scenarios leading to more valid votes. Blank and particularly null voting are found to be more prevalent in municipalities where a second round is possible. Economic factors and age categories also contribute to determine unconventional voting patterns. The results also highlight important differences between blank and null voting patterns and between urban and rural areas, the later suggesting that more sophisticated voters tend to be less prone to invalidate the vote.